Gendered Citizenships
XXI, 225 p.
Keywords: Drawing on ethnographic research with underrepresented communities in the Caribbean, Europe, South America, and the United States, this wide-ranging anthology examines the gendered dimensions of citizenship experiences and uses them as a point of departure for rethinking contemporary practices of social inclusion and national belonging.